2008
DOI: 10.1111/j.1742-4658.2008.06570.x
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Reed–Sternberg cells express 15‐lipoxygenase‐1 and are putative producers of eoxins in vivo

Abstract: Classical Hodgkin lymphoma has unique clinical and pathological features and tumour tissue is characterized by a minority of malignant Hodgkin Reed–Sternberg cells surrounded by inflammatory cells. In the present study, we report that the Hodgkin lymphoma‐derived cell line L1236 has high expression of 15‐lipoxygenase‐1 and that these cells readily convert arachidonic acid to eoxin C4, eoxin D4 and eoxin E4. These mediators were only recently discovered in human eosinophils and mast cells and found to be potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…A second paper demonstrated that 15-LOX was strongly expressed in Hodgkin Reed-Sternberg cells and pointed to the importance of LOX as potential therapeutic targets in malignant hemopathies. In this same study, the authors confirmed the absence of 15-LOX mRNA in several non-Hodgkin's lymphomas, but the role of ROS or LOX enzymes in ALCLs has so far never been investigated (Claesson et al, 2008).…”
mentioning
confidence: 63%
“…A second paper demonstrated that 15-LOX was strongly expressed in Hodgkin Reed-Sternberg cells and pointed to the importance of LOX as potential therapeutic targets in malignant hemopathies. In this same study, the authors confirmed the absence of 15-LOX mRNA in several non-Hodgkin's lymphomas, but the role of ROS or LOX enzymes in ALCLs has so far never been investigated (Claesson et al, 2008).…”
mentioning
confidence: 63%
“…LTB4 has been shown to impact the immune response and spread of viral infections, including those caused by HIV, respiratory syncytial virus, and Epstein-Barr virus (EBV) (44)(45)(46)(47)(48)(49). 5LO, LTA4H, and LTB4 are found at high levels in most of the inflammation and oxidative stress-associated cancers, such as breast, lung, prostate, pancreatic, colon, bladder, esophageal, and testicular cancers; glioma; chronic myelogenous leukemia; and Mantle cell lymphoma (MCL) non-Hodgkin's lymphomas (41,42,(50)(51)(52)(53)(54). 5LO pathway inhibitors have been tested as chemoprevention agents in many cancers (55,56).…”
mentioning
confidence: 99%
“…7 We have used this cell assay to develop a microplate assay that is amenable for screening and for determination of inhibitory potency. To establish basic assay conditions, we titrated the amount of substrate and also investigated the linearity of product formation with respect to incubation time (Suppl.…”
Section: Development and Validation Of A Cell-based Assay In A 96-or mentioning
confidence: 99%
“…9,10 Ovalbumin-sensitized 12/15-LO null mice display reduced airway inflammation, reduced cytokine production, and less proliferation of airway epithelial cells after exposure of allergen. 11,12 There are also reports suggesting that 15-LO-1 is involved in pathological processes such as cytokine release from airway epithelial cells, 13 cardiac inflammation, 14 atherosclerosis, [15][16][17] Alzheimer's disease, 18 Hodgkin's lymphoma, 7 and latent insulin resistance and diabetic nephropathy. 19,20 Also, 15-LO-1 inhibitors have been shown to rescue neuronal cells from cell death induced by oxidative stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation